2018
DOI: 10.1111/jth.13978
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin‐reduced miR‐27b attenuates platelet angiogenic activities in vitro via enhancing platelet synthesis of anti‐angiogenic thrombospondin‐1

Abstract: Background Platelets can synthesize proteins upon activation. Platelets contain a number of microRNAs (miRNA) and a fully functional miRNA effector machinery. It is, however, unclear if platelet miRNAs can regulate protein synthesis of platelets, and whether the regulation may produce a physiological impact. Objectives To investigate if and how platelet miRNAs regulate de novo syntheses of angiogenic regulators and subsequently modulate platelet angiogenic activities. Methods and Results Microarray-based miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Recently, the potential role of miRNAs in platelet and MK function has also got in focus [25,33]. For instance, platelet miR-27b can regulate platelet synthesis of trombospondin-1 [19], or miR-15a modulates GPVI-mediated αIIbβ3 activation and α-granule release in MKs [34]. In sepsis, there was only one former publication, which reported impaired miRNA levels in exosomes and pooled human blood cells but not in platelets [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the potential role of miRNAs in platelet and MK function has also got in focus [25,33]. For instance, platelet miR-27b can regulate platelet synthesis of trombospondin-1 [19], or miR-15a modulates GPVI-mediated αIIbβ3 activation and α-granule release in MKs [34]. In sepsis, there was only one former publication, which reported impaired miRNA levels in exosomes and pooled human blood cells but not in platelets [35].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of altered miRNAs correlates with platelet reactivity [17], while Dicer1-mediated miRNAs are able to regulate target mRNAs and de novo synthesis of proteins being important for the hemostatic function of platelets [18]. Accordingly, the expression of RNAs and related proteins are not static in platelets and can be modulated upon platelet activation [19]. Among in vitro septic conditions, mRNA levels of IL1B (interleukin-1β, IL-1β) and F3 (tissue factor) are increased, and resulting proteins are translated and accumulated in human platelets in response to TLR4 agonist lipopolysaccharide (LPS) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have identified a number of miRNAs that regulate the THBS1 gene in different types of cells, e.g., miR‐487b, the miR‐17‐92 cluster, miR‐194, miR‐18 and miR‐19, miR‐27b, and miR‐let‐7d (Asama et al, ; Dogar, Semplicio, Guennewig, & Hall, ; Farberov & Meidan, ; Feng et al, ; Miao et al, ; Sundaram et al, ; van Almen et al, ). In a recent study, a quantitative proteomic analysis of PK‐15 cells that were transfected with miR‐222 mimics and infected with transmissible gastroenteritis virus (TGEV) indicated that THBS1 was regulated by miR‐222 (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MVs also deliver angiogenic signals [27]: Transfer of miRNA let-7a or miR-27b in endothelial cells down-regulates the expression of the anti-angiogenic modulator thrombospondin-1, thus enhancing platelet-dependent endothelial tube formation [168,169].…”
Section: Platelet Microvesicle-derived Mirnasmentioning
confidence: 99%